Spot the difference: Zircon disparity tracks crustal evolution - Barham, Milo; Kirkland, Chris; Hollis, Julie (GEOLOGICAL SOC AMER, INC, 2019)
© 2019 Geological Society of America. We present a novel approach to examining the detrital zircon record, using similarity analysis of regionally defined populations to track crust production, preservation, and the efficacy of crustal recycling and homogenization. We compared temporally binned detrital zircon age data from geographically defined regions using Kolmogorov-Smirnov similarity measures, multidimensional scaling, and cluster analysis. This approach tracks disparity in the global detrital zircon record from 4 Ga to the present. Disparity values increase dramatically in the Neoarchean and are interpreted to reflect the emergence and preservation of isolated crustal fragments. Disparity values decrease through the early Paleoproterozoic, associated with the onset of plate tectonics and craton assembly. Oscillating disparity values through the remaining Proterozoic and Phanerozoic correlate ( p = < 0.01) with the supercontinent cycle, where regional detrital zircon populations are more similar during assembly and more distinct during dispersal. This link between the detrital zircon record and the supercontinent cycle necessitates well-coupled crustal recycling mechanisms that operate via both magmatic and sedimentary processes.